Spatial/Territorial Development Policies in the United States - Hewings, Geoffery J.D. (Washington, DC: World Bank, 2012)
Regional development policies in the United States are a complex web of (often poorly) integrated programs that stretch across a vast array of federal, state and local government agencies and that operate at different and often overlapping spatial scales. These programs have changed dramatically over the past three or four decades, largely in response to changes in spatial organization of production generated by public and private investment strategies adopted by firms exploring broader options in their location decision-making. Complementing these changes is an array of demand and supply pressures generated by globalization. As a consequence, different stages in the spatial development process in the US have called forth a different set of formal and hidden policies. Currently, the transformation to a new stage is moving rapidly although the degree of coordination across spatial governance regimes is often ad hoc at best.